Silicon carbide treatment method and silicon carbide reinforced aluminum-based composite material
By pickling silicon carbide particles with high-concentration hydrofluoric acid to change their surface properties and improve their interface bonding with the aluminum alloy matrix, the problem of improving the performance of existing silicon carbide-reinforced aluminum-based composite materials is solved, and the strength and strength of the aluminum-based composite materials are improved. Significant improvement in elastic modulus and thermal diffusivity.
Patent Information
- Application Number
- CN202411516017.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-24
AI Technical Summary
There is room for performance improvement in existing silicon carbide-reinforced aluminum-based composite materials in structural bearing, thermal control and anti-resonance functions, especially in terms of strength, elastic modulus and thermal diffusion coefficient.
High-concentration hydrofluoric acid is used to immerse silicon carbide particles for a long time and undergo heavy pickling treatment to change the chemical and physical properties of the surface, thereby improving the interface bonding state between silicon carbide and the aluminum alloy matrix.
Through this method, the strength, elastic modulus and thermal diffusion coefficient of silicon carbide reinforced aluminum matrix composites are significantly improved, improving its performance in application scenarios such as aerospace precision instruments and electronic component packaging.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal matrix composite materials, and in particular to a silicon carbide processing method and a silicon carbide reinforced aluminum matrix composite material. Background Art
[0002] The characteristics of low expansion, high specific modulus, high thermal conductivity, and high resonant frequency make high volume fraction ceramic particle reinforced aluminum-based composites have excellent structural bearing function, excellent thermal control function, and unique anti-resonance function. Taking high volume fraction (55%) silicon carbide particle reinforced aluminum-based composites as an example, its specific modulus can reach three times that of aluminum alloy and titanium alloy, and its thermal expansion coefficient is less than 40% of that of aluminum alloy, which is lower than that of titanium alloy. The average resonant frequency is more than 60% higher than that of aluminum, titanium, and steel, three commonly used metal structural materials, and the thermal conductivity is much higher than that of aluminum alloy. This new material with the comprehensive performance advantages of structural / functional integration has been applied in batches in my country's aerospace precision instruments and military electronic components, and has achieved remarkable application results.
[0003] Pressureless infiltration is an effective process for preparing high volume fraction ceramic particle reinforced aluminum matrix composites. It not only has a short process flow, high production efficiency, uniform distribution of ceramic particles in the aluminum alloy matrix, good billet size stability, but also is relatively easy to achieve large-scale preparation. The high volume fraction silicon carbide reinforced aluminum matrix composites prepared by pressureless infiltration are used as precision instrument components to further improve their strength, elastic modulus and thermal diffusivity, which is undoubtedly of great significance and engineering value. Summary of the invention
[0004] The purpose of the present invention is to provide a silicon carbide processing method and a silicon carbide reinforced aluminum-based composite material, by chemically etching silicon carbide to change the chemical and physical properties of the silicon carbide surface, thereby improving the interface bonding state between silicon carbide and aluminum alloy matrix, and improving the strength, elastic modulus and thermal diffusion coefficient of the silicon carbide reinforced aluminum-based composite material.
[0005] To achieve the above object, the present invention provides a method for processing silicon carbide, comprising the following steps: S1. Using high concentration acid to soak the silicon carbide particles for a long time for heavy pickling treatment; S2, washing the pickled silicon carbide particles with water until they are neutral; S3, drying the washed silicon carbide particles to obtain activated silicon carbide particles.
[0006] Preferably, in S1, the high concentration acid is hydrofluoric acid having a mass percentage concentration of 20% to 49%.
[0007] Preferably, in S1, the time of long-term immersion and heavy pickling treatment is 24h~96h.
[0008] Preferably, in S1, the median particle size D50 of the silicon carbide particles is 3 μm to 120 μm.
[0009] Preferably, in S1, the purity of the silicon carbide particles is not less than 99.5%.
[0010] Preferably, in S2, the silicon carbide particles are washed with deionized water.
[0011] Preferably, in S3, the drying temperature is 120° C. to 150° C., and the drying time is 60 min to 180 min.
[0012] A silicon carbide reinforced aluminum-based composite material comprises an aluminum alloy matrix, in which the activated silicon carbide particles obtained above are compounded.
[0013] Preferably, the volume fraction of the activated silicon carbide particles is 40% to 70%.
[0014] Preferably, the aluminum alloy is an aluminum-silicon-magnesium casting aluminum alloy.
[0015] The method for preparing the above silicon carbide reinforced aluminum-based composite material comprises the following steps: The activated silicon carbide particles are piled up in a graphite crucible into a pile with a packing density of 40% to 70%, and the upper surface of the pile is flattened. The silicon carbide particles can be piled up by pressing or vibrating so that the silicon carbide particles are tightly piled up without connection between the silicon carbide particles. The frequency of the silicon carbide particle pile compaction is set according to the pre-designed silicon carbide particle packing density and the projected area and height of the pile, and the pressure of the silicon carbide particle pressing is also set according to the silicon carbide particle packing density and the projected area and height of the pile.
[0016] Aluminum alloy ingots are placed on the upper surface of the deposit. The amount of aluminum alloy ingots is calculated based on the volume of the silicon carbide particle deposit and the porosity of the deposit. The actual amount of aluminum alloy is 10% to 20% more than the calculated theoretical amount.
[0017] Put the graphite crucible, the silicon carbide particle stack and the aluminum alloy ingot into a heating furnace, heat and keep warm under the protection of nitrogen atmosphere, the heating temperature is 800℃~950℃, the heat preservation time is 2h~15h. Cool to room temperature to obtain the silicon carbide reinforced aluminum matrix composite material.
[0018] Silicon carbide particles are materials with very stable properties. Generally, silicon carbide particles do not react with acid. High concentrations of hydrofluoric acid are highly corrosive and have a strong corrosive effect on silicon-containing substances. When silicon carbide is immersed in high concentrations of hydrofluoric acid for a long time, the following changes will occur on the surface of silicon carbide: first, the fluoride ions (F⁻) in hydrofluoric acid will react to a certain extent with the silicon atoms (Si) on the surface of silicon carbide, resulting in partial breakage of the Si-C bond; second, the fluoride ions will combine with the silicon atoms or carbon atoms on the surface of silicon carbide to form new fluorine-containing chemical bonds. The newly formed fluorine-containing chemical bonds and the partial breakage of the Si-C bonds will affect the chemical and physical properties of the surface of silicon carbide particles, improve the wettability and chemical reaction activity with aluminum liquid, thereby enhancing the interface bonding between silicon carbide particles and aluminum matrix, improving its load transfer efficiency, and reducing the interface thermal resistance. The macroscopic manifestation is the improvement of the strength, elastic modulus and thermal diffusion coefficient of aluminum-based composite materials.
[0019] In the prior art, low-concentration acidic solutions are also used to treat silicon carbide, but the existing low-concentration acidic solution is used to treat silicon carbide in order to remove impurities mixed in during the powder processing or adhered to the surface of silicon carbide particles or to remove the amorphous silicon dioxide thin layer on the surface of silicon carbide, so as to improve the purity of silicon carbide and obtain high-purity silicon carbide particles. The above operation will not affect the silicon carbide body (including its surface). The silicon carbide used in the present invention is high-purity silicon carbide particles after conventional treatment, and the high-purity silicon carbide particles are surface activated to improve the bonding strength between the silicon carbide particles and the aluminum alloy, thereby improving the performance of the silicon carbide reinforced aluminum-based composite material.
[0020] The advantages and positive effects of the silicon carbide processing method and the silicon carbide reinforced aluminum-based composite material described in the present invention are: 1. The present invention uses high-concentration hydrofluoric acid to perform a long-term immersion and heavy pickling treatment on silicon carbide particles, thereby changing the chemical and physical properties of the surface of the silicon carbide particles, promoting the bonding of the silicon carbide particles with the aluminum alloy matrix, and improving the strength, elastic modulus and thermal diffusion coefficient of the aluminum-based composite material. The application efficiency of silicon carbide reinforced aluminum-based composite materials in typical application scenarios such as aerospace precision instruments and electronic component packaging is improved, and the components are endowed with higher structural accuracy stability and heat dissipation capacity.
[0021] 2. The silicon carbide particle processing method of the present invention is simple and easy to operate, has low cost, and the surface of the silicon carbide particles is evenly treated, and is easy to realize industrial production.
[0022] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION
[0023] In the description of the present invention, it should be noted that, unless otherwise specified, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art in the art. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0024] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0025] The technical solution of the present invention is described in detail below through embodiments.
[0026] Example 1 S1. The silicon carbide particles are subjected to a long-term heavy pickling treatment by immersing in hydrofluoric acid with a mass percentage concentration of 20%, and the immersion time is 96 hours. The median particle size (D50) of the silicon carbide particles is 90 μm.
[0027] S2. Wash the pickled silicon carbide particles with deionized water until they are neutral.
[0028] S3. Drying the washed silicon carbide particles at a temperature of 120° C. for 180 min to obtain activated silicon carbide particles.
[0029] Activated silicon carbide particles are loaded into a graphite crucible to form a pile with a packing density of 55%, and the upper surface of the pile is flattened with a glass plate. An aluminum-silicon-magnesium cast aluminum alloy ingot is placed on it, and the actual amount of the aluminum alloy ingot is 10% to 20% more than the theoretical amount calculated based on the volume of the pile and the porosity of the pile (45%). The graphite crucible and its contents are placed in a heating device with a nitrogen atmosphere and heated to 850°C for 8 hours. Then it is cooled to room temperature, and the contents are removed from the graphite crucible to obtain a silicon carbide reinforced aluminum-based composite material ingot.
[0030] Example 2 S1. The silicon carbide particles were subjected to a long-term heavy pickling treatment by immersing in hydrofluoric acid with a mass percentage concentration of 30% for 72 hours. The median particle size (D50) of the silicon carbide particles was 12.8 μm.
[0031] S2. Wash the pickled silicon carbide particles with deionized water until they are neutral.
[0032] S3, drying the washed silicon carbide particles at a temperature of 130° C. for 150 min to obtain activated silicon carbide particles.
[0033] Activated silicon carbide particles are loaded into a graphite crucible to form a pile with a packing density of 45%, and the upper surface of the pile is flattened with a glass plate. An aluminum-silicon-magnesium cast aluminum alloy ingot is placed on it, and the actual amount of the aluminum alloy ingot is 10% to 20% more than the theoretical amount calculated based on the volume of the pile and the porosity of the pile (55%). The graphite crucible and its contents are placed in a heating device with a nitrogen atmosphere and heated to 880°C for 6 hours. Then it is cooled to room temperature, and the contents are removed from the graphite crucible to obtain a silicon carbide reinforced aluminum-based composite material ingot.
[0034] Example 3 S1. The silicon carbide particles are subjected to a long-term heavy pickling treatment by immersing in hydrofluoric acid with a mass percentage concentration of 35% for 60 hours. The median particle size (D50) of the silicon carbide particles is 120 μm.
[0035] S2. Wash the pickled silicon carbide particles with deionized water until they are neutral.
[0036] S3, drying the washed silicon carbide particles at a temperature of 140° C. for 120 min to obtain activated silicon carbide particles.
[0037] Activated silicon carbide particles are loaded into a graphite crucible to form a pile with a packing density of 63%, and the upper surface of the pile is flattened with a glass plate. An aluminum-silicon-magnesium cast aluminum alloy ingot is placed on it, and the actual amount of the aluminum alloy ingot is 10% to 20% more than the theoretical amount calculated based on the volume of the pile and the porosity of the pile (37%). The graphite crucible and its contents are placed in a heating device with a nitrogen atmosphere and heated to 800°C for 15 hours. Then it is cooled to room temperature, and the contents are removed from the graphite crucible to obtain a silicon carbide reinforced aluminum-based composite material ingot.
[0038] Example 4 S1. The silicon carbide particles are subjected to a long-term heavy pickling treatment by immersing in hydrofluoric acid with a mass percentage concentration of 40% for 36 hours. The median particle size (D50) of the silicon carbide particles is 3 μm.
[0039] S2. Wash the pickled silicon carbide particles with deionized water until they are neutral.
[0040] S3, drying the washed silicon carbide particles at a temperature of 150° C. for 90 min to obtain activated silicon carbide particles.
[0041] Activated silicon carbide particles are loaded into a graphite crucible to form a pile with a packing density of 40%, and the upper surface of the pile is flattened with a glass plate. An aluminum-silicon-magnesium cast aluminum alloy ingot is placed on it, and the actual amount of the aluminum alloy ingot is 10% to 20% more than the theoretical amount calculated based on the volume of the pile and the porosity of the pile (60%). The graphite crucible and its contents are placed in a heating device with a nitrogen atmosphere and heated to 950°C for 2 hours. Then it is cooled to room temperature, and the contents are removed from the graphite crucible to obtain a silicon carbide reinforced aluminum-based composite material ingot.
[0042] Example 5 S1. The silicon carbide particles are subjected to a long-term heavy pickling treatment by immersing in hydrofluoric acid with a mass percentage concentration of 49% for 24 hours. The silicon carbide particles are composed of two median particle sizes (D50) of 75µm and 17.3µm mixed in a ratio of 8:2.
[0043] S2. Wash the pickled silicon carbide particles with deionized water until they are neutral.
[0044] S3, drying the washed silicon carbide particles at a temperature of 150° C. for 60 min to obtain activated silicon carbide particles.
[0045] Activated silicon carbide particles are loaded into a graphite crucible to form a pile with a packing density of 70%, and the upper surface of the pile is flattened with a glass plate. An aluminum-silicon-magnesium cast aluminum alloy ingot is placed on it, and the actual amount of the aluminum alloy ingot is 10% to 20% more than the theoretical amount calculated based on the volume of the pile and the porosity of the pile (30%). The graphite crucible and its contents are placed in a heating device with a nitrogen atmosphere and heated to 920°C for 4 hours. Then it is cooled to room temperature, and the contents are removed from the graphite crucible to obtain a silicon carbide reinforced aluminum-based composite material ingot.
[0046] Comparative Example 1 The only difference between this comparative example and Example 1 is that the silicon carbide particles are not soaked in hydrofluoric acid but used directly. The specific steps are: Silicon carbide particles are loaded into a graphite crucible to form a pile with a packing density of 55%, and the upper surface of the pile is flattened with a glass plate. An aluminum-silicon-magnesium cast aluminum alloy ingot is placed on it, and the actual amount of the aluminum alloy ingot is 10% to 20% more than the theoretical amount calculated based on the volume of the pile and the porosity of the pile (45%). The graphite crucible and its contents are placed in a heating device with a nitrogen atmosphere and heated to 850°C for 8 hours. Then it is cooled to room temperature, and the contents are removed from the graphite crucible to obtain a silicon carbide reinforced aluminum-based composite material ingot.
[0047] The median particle size (D50) of the silicon carbide particles was 90 μm.
[0048] Comparative Example 2 The only difference between this comparative example and Example 2 is that the silicon carbide particles are not soaked in hydrofluoric acid but used directly. The specific steps are: Silicon carbide particles are loaded into a graphite crucible to form a pile with a packing density of 45%, and the upper surface of the pile is flattened with a glass plate. An aluminum-silicon-magnesium cast aluminum alloy ingot is placed on it, and the actual amount of the aluminum alloy ingot is 10% to 20% more than the theoretical amount calculated based on the volume of the pile and the porosity of the pile (55%). The graphite crucible and its contents are placed in a heating device with a nitrogen atmosphere and heated to 880°C for 6 hours. Then it is cooled to room temperature, and the contents are removed from the graphite crucible to obtain a silicon carbide reinforced aluminum-based composite material ingot.
[0049] The median particle size (D50) of the silicon carbide particles was 12.8 μm.
[0050] Comparative Example 3 The only difference between this comparative example and Example 3 is that the silicon carbide particles are not soaked in hydrofluoric acid but used directly. The specific steps are: Silicon carbide particles are loaded into a graphite crucible to form a pile with a packing density of 63%, and the upper surface of the pile is flattened with a glass plate. An aluminum-silicon-magnesium cast aluminum alloy ingot is placed on it, and the actual amount of the aluminum alloy ingot is 10% to 20% more than the theoretical amount calculated based on the volume of the pile and the porosity of the pile (37%). The graphite crucible and its contents are placed in a heating device with a nitrogen atmosphere and heated to 800°C for 15 hours. Then it is cooled to room temperature, and the contents are removed from the graphite crucible to obtain a silicon carbide reinforced aluminum-based composite material ingot.
[0051] The median particle size (D50) of the silicon carbide particles was 120 μm.
[0052] Comparative Example 4 The only difference between this comparative example and Example 4 is that the silicon carbide particles are not soaked in hydrofluoric acid but used directly. The specific steps are: Silicon carbide particles are loaded into a graphite crucible to form a pile with a packing density of 40%, and the upper surface of the pile is flattened with a glass plate. An aluminum-silicon-magnesium cast aluminum alloy ingot is placed on it, and the actual amount of the aluminum alloy ingot is 10% to 20% more than the theoretical amount calculated based on the volume of the pile and the porosity of the pile (60%). The graphite crucible and its contents are placed in a heating device with a nitrogen atmosphere and heated to 950°C for 2 hours. Then it is cooled to room temperature, and the contents are removed from the graphite crucible to obtain a silicon carbide reinforced aluminum-based composite material ingot.
[0053] The median particle size (D50) of the silicon carbide particles was 3 μm.
[0054] Comparative Example 5 The only difference between this comparative example and Example 5 is that the silicon carbide particles are not soaked in hydrofluoric acid but used directly. The specific steps are: Silicon carbide particles are loaded into a graphite crucible to form a pile with a packing density of 70%, and the upper surface of the pile is flattened with a glass plate. An aluminum-silicon-magnesium cast aluminum alloy ingot is placed on it, and the actual amount of the aluminum alloy ingot is 10% to 20% more than the theoretical amount calculated based on the volume of the pile and the porosity of the pile (30%). The graphite crucible and its contents are placed in a heating device with a nitrogen atmosphere and heated to 920°C for 4 hours. Then it is cooled to room temperature, and the contents are removed from the graphite crucible to obtain a silicon carbide reinforced aluminum-based composite material ingot.
[0055] The silicon carbide particles are composed of particles with a median particle size (D50) of 75µm and 17.3µm mixed in a ratio of 8:2.
[0056] The performance tests were performed on the silicon carbide reinforced aluminum-based composite material ingots obtained in Examples 1 to 5 and Comparative Examples 1 to 5, and the results are shown in Table 1, Table 2, Table 3, Table 4, and Table 5, respectively.
[0057] Table 1 Measured values of composite material performance indicators obtained in Example 1 and Comparative Example 1
[0058] Table 2 Measured values of composite material performance indicators obtained in Example 2 and Comparative Example 2
[0059] Table 3 Measured values of composite material performance indicators obtained in Example 3 and Comparative Example 3
[0060] Table 4 Measured values of composite material performance indicators obtained in Example 4 and Comparative Example 4
[0061] Table 5 Measured values of composite material performance indicators obtained in Example 5 and Comparative Example 5
[0062] From the performance test results of the silicon carbide reinforced aluminum-based composite material ingots obtained in Examples 1 to 5 and Comparative Examples 1 to 5, it can be seen that after the silicon carbide particles are soaked in high-concentration hydrofluoric acid for a long time and then pickled, the bending strength, bending elastic modulus and thermal diffusion coefficient of the obtained silicon carbide reinforced aluminum-based composite material are significantly improved.
[0063] Therefore, by adopting the silicon carbide processing method and silicon carbide reinforced aluminum-based composite material described in the present invention, the silicon carbide is chemically corroded and the chemical and physical properties of the silicon carbide surface are changed, thereby improving the interface bonding state between the silicon carbide and the aluminum alloy matrix, and effectively improving the strength, elastic modulus and thermal diffusion coefficient of the silicon carbide reinforced aluminum-based composite material.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for processing silicon carbide, characterized in that: The following steps are involved: S1. Using high concentration acid to soak the silicon carbide particles for heavy pickling treatment; S2, washing the pickled silicon carbide particles with water until they are neutral; S3, drying the washed silicon carbide particles to obtain activated silicon carbide particles.
2. A method for processing silicon carbide according to claim 1, characterized in that: In the S1, the high concentration acid is hydrofluoric acid with a mass percentage concentration of 20% to 49%.
3. A method for processing silicon carbide according to claim 1, characterized in that: In S1, the immersion time for the heavy pickling treatment is 24h to 96h.
4. A method for processing silicon carbide according to claim 1, characterized in that: In the S1, the median particle size D50 of the silicon carbide particles is 3 μm to 120 μm.
5. A method for processing silicon carbide according to claim 1, characterized in that: In the S1, the purity of the silicon carbide particles is not less than 99.5%.
6. A method for processing silicon carbide according to claim 1, characterized in that: In S2, the silicon carbide particles are washed with deionized water.
7. A method for processing silicon carbide according to claim 1, characterized in that: In S3, the drying temperature is 120° C. to 150° C., and the drying time is 60 min to 180 min.
8. A silicon carbide reinforced aluminum-based composite material, characterized in that: The invention comprises an aluminum alloy matrix, wherein the aluminum alloy matrix is compounded with activated silicon carbide particles obtained by the silicon carbide treatment method according to any one of claims 1 to 7.
9. The silicon carbide reinforced aluminum-based composite material according to claim 8, characterized in that: The volume fraction of the activated silicon carbide particles is 40% to 70%.
10. The silicon carbide reinforced aluminum-based composite material according to claim 8, characterized in that: The aluminum alloy is an aluminum-silicon-magnesium casting aluminum alloy.